Safety and Efficacy of All Comers Treated with a Paclitaxel Coated Balloon for Below Knee Intervention. (November 2022) - Wittig, Tim; Schmidt, Andrej; Kabelitz, Maria; Hukauf, Martin; Pflug, Toni; Scheinert, Dierk; Steiner, Sabine
Abstract : Objective: Data on paclitaxel coated balloons (PCBs) for below knee (BTK) angioplasty exhibited conflicting efficacy results, and previous meta-analyses suggested an increased mortality and amputation risk highlighting the need for further research. The aim of this study was to investigate safety and efficacy of PCBs for BTK interventions in a real world cohort. Methods: Within a single centre cohort study, 552 consecutive patients were included undergoing BTK interventions with and without PCB use. Two year safety and efficacy results were compared in unadjusted and propensity score matched (PSM) analysis. Results: BTK interventions were performed in 157 patients with PCB angioplasty (100% Lutonix 0.014 inch drug coated balloon; Bard Lutonix, New Hope, MN, USA) and 395 patients with plain old balloon angioplasty (POBA). The majority of interventions (> 70%) were performed for chronic limb threatening ischaemia. Mean lesion length was 20.8 ± 12.6 cm; 61.2% in the PCB and 66.7% in the POBA group were occlusions. In the PCB group, more procedures were performed for re-stenotic lesions than POBA (28.5 vs. 17.2%). In PSM analysis (128 matched pairs), the primary efficacy endpoint was freedom from clinically driven target lesion revascularisation (CD TLR), which occurred in 70.1% in the PCB and 73.1% in the POBA group at one year ( p  = .85; McNemar test). Survival analysis suggested lower rates of major amputations in the PCB group in unadjusted (94.4% ± 2.1 vs. 89.2% ± 1.9 in the POBA group) and PSM analyses (97.2% ± 1.6 vs. 89.3% ± 3.5) through two years, while no differences were seen for CD TLR and all cause mortality between the groups. Conclusion: In this all comer analysis, PCBs were found to be safe for BTK interventions with a signal towards lower amputation rates but no benefit was seen for repeat revascularisation.